Motivation contribution to religious learning behavior during the covid pandemic - Adi Atmoko; Masyhuri Machfudz; Rosichin Mansur; Augusto Da Costa (Jurnal Cakrawala Pendidikan, 2022)
The Indonesian Minister of Education designed the 2013 school curriculum (K13) to activate students’ learning behavior but there is low-intensity research in it. Hence, this study aims to explain the contribution of achievement, affiliation, power, and religious motivation to learning behavior in Islamic Religion that applies K13 during the pandemic in adolescent students. It employed a causal relationship-explanation design involving 201 samples selected through random stratification representing 795 student population aged 13-16 years, grades 7th, 8th, and 9th from 26 parallel classes. Data were collected through a five scales test for item validity ≥ 0.3 and Cronbach Alpha reliability by 0.6 - 0.904, and then analyzed via multiple regression. The results showed that the theoretical regression model was empirically fit (sig F (201) = 0.000 0.05). The contribution of the four predictor motivations in the model together was 72.9 percent on learning behavior. Achievement, affiliation, and religious motivation could contribute in increasing learning behavior, but power motivation demonstrated otherwise. Consequently, teachers need to guide adolescent students to increase achievement motivation, religion, and affiliation but reduce power motivation at an ideal level to improve student learning behavior.